Motivation Of Dryland Utilization On Integrated Farming In East Lombok - Pande Komang Suparyana; Aeko Fria Utama FR; Putu Eka Pasmidi Ariati (SOCA: Jurnal Sosial Ekonomi Pertanian, 2020)
Utilization of the dryland farming resources through the integration of the farming and livestock is an alternative to improve the farmer income. This study aimed to analyze the effect of variables on the utilization of the dryland and analyze the effect of those variables on the farmer’s motivation in conducting the integration of farming and livestock simultaneously and partially in Gunung Malang Village, Pringgabaya District. There were 82 farmers from 11 farmer institutional group in Gunung Malang Village, Pringgabaya District, East Lombok Regency involved in this study. This study was employed a multiple regression analysis to processed the data. Results showed that the livestock, value-added to the livestock, land-area, farming experience, education level, and the number of the family member variable simultaneously affected the farmer motivation in implementing the farming and livestock integration in Gunung Malang Village. While the livestock capital, farming experience, and the number of the family member variable partially affected the farmer motivation in implementing the farming and livestock integration. The land-area and educational level didn’t contribute significantly to the implementation of farming and livestock integration in Gunung Malang Village.